#TITLE_ALTERNATIVE# - FAUZY HARAHAP (NIM : 25007022); Pembimbing : Prof. Dr. Ir. M. Syahril B.K.; Dhemi Harlan, Ph, IRPAN
Construction of dams has benefits and potential dangers to humans life. Benefits to be received from the construction of such dams is for water supply, hydropower, flood control and others. The potential dangers can happen when a dam failure that could lead to catastrophe in downstream areas, such as flooding. The case of floods in the downstream caused by dam failure (dam-break) has some interesting things that need to be explored further because it deals with human lives and infrastructure that supports human life. The direction of flow was no longer completely dependent on the topography of land, because of the buildings that block the flow direction. Flow was turned toward because hitting the building. Development of numerical model is intended to identify propagation / 2-dimensional flow propagation between buildings due to dam break. Modeling is done by using St. Venant 2 Dimension as the governing equations, which were completed with Mac Cormack finite difference method. Factors affecting the flow are land cover and land slope/contour. Surface runoff that occurs is caused by the discharge from the dam break. The buildings that located at downstream of dam is modeled as an impervious wall where the velocity direction perpendicular to the wall equal to zero or can also modeled as a contour (elevation of the building) and provide manning a certain value. Roughness of the channel / flume or buildings provided certain manning coefficient value. Wet dry conditions on the model given by specifying a minimum depth of flow. Modelling carried out by several configuration shapes and positions of different buildings using a fixed discharge. From this model the resulting flow profile as a function of velocity, water level and flow direction.